2018
DOI: 10.1021/acssuschemeng.8b05302
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrodeposition of Phosphorus-Doped Nickel Superstructures from Choline Chloride–Ethylene Glycol Deep Eutectic Solvent for Enhanced Hydrogen Evolution Catalysis

Abstract: Hydrogen produced by electrochemical water splitting offers a hopeful and renewable solution to address the global energy crisis; however, development of highly efficient hydrogen generation electrocatalysts remains a big challenge. Herein, self-supported P-doped nickel superstructure films (NiP x ) developed on Cu foil were prepared via a facile one-step electrodeposition route from the choline chloride−ethylene glycol (Ethaline)-based deep eutectic solvent (DES). Two depositional patterns including potentios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 64 publications
(81 reference statements)
1
17
0
Order By: Relevance
“…A two-electrode water electrolyzer using Ni-P/CF as cathode and anode produces 10 mA/cm 2 at a cell voltage of 1.68 V with high stability. Sun et al prepared P-doped nickel (NiP x ) superstructure films on Cu foil by potentio-static deposition (PSD) and potentio-dynamic (PDD) approach, respectively [135]. By comparing the two deposition methods, it is found that the latter model with a potentio-dynamic control is a valid electrochemical protocol to create crack-free NiP x films.…”
Section: Electrochemical Depositionmentioning
confidence: 99%
“…A two-electrode water electrolyzer using Ni-P/CF as cathode and anode produces 10 mA/cm 2 at a cell voltage of 1.68 V with high stability. Sun et al prepared P-doped nickel (NiP x ) superstructure films on Cu foil by potentio-static deposition (PSD) and potentio-dynamic (PDD) approach, respectively [135]. By comparing the two deposition methods, it is found that the latter model with a potentio-dynamic control is a valid electrochemical protocol to create crack-free NiP x films.…”
Section: Electrochemical Depositionmentioning
confidence: 99%
“…Other DES-type ILs were examined Gong et al [80] and Sun et al [74]. Gong Later, the same choline-based mixture was applied by Cherigui et al [72] for electrodeposition of Ni nanostructures onto a glassy carbon electrode.…”
Section: Nickel (Ni)mentioning
confidence: 99%
“…Other DES-type ILs were examined Gong et al [80] and Sun et al [74]. Gong The coatings were obtained at various potentials (Figure 3).…”
Section: Nickel (Ni)mentioning
confidence: 99%
See 1 more Smart Citation
“…Photocatalysis is a catalysis process that is used to provide sustainable solutions in several different fields such as biorefinery [1], organocatalysis [2], waste valorization [3], hydrogen evolution [4] and water purification [5].…”
Section: Introductionmentioning
confidence: 99%